The Beginning of medical genetics: Solomon Grigorevich Levit and his scientific school - R. O. Fando (History of science and technology, 2015)
The article considers medical genetic studies carried out by S.G. Levit scientifi c School. The workers of the Medical biologic institute studied geographical prevalence of different forms of colorblindness, early canities and surdomutism. The hospital examination of twins was another direction of research studies of Levit School. The organization of the mentioned research was clear-cut planned. The groups of researchers were organized to study normal and pathologic characteristics. The special research program was developed. The institute permanently carried out active workshops and conferences, published scientifi c transactions. The consolidation of various specialists around the scientifi cschool made it possible to resolve many inter-disciplinary problems in the fi eld of inherent pathology.